Pengajian Falsafah Islam di Institusi Pengajian Tinggi Awam di Malaysia: Sukatan, Masalah dan Cabaran Pengajian - Wan Abdullah, Wan Suhaimi (Afkar: Jurnal Akidah dan Pemikiran Islam, 2006)
This article attempts to identify the problems and the challenges faced by Malaysian Higher Educational Institutions in teaching philosophy and particularly the Islamic Philosophy. Two syllabi were compared in this study, namely the syllabus of the Department of 'Aqidah and Islamic Thought, Academy of Islamic Studies, University of Malaya and of the Department of Theology and Philosophy, Faculty of Islamic Studies, National University of Malaysia. The content as well as its credit hours in both syllabi are analysed. The article begins with a view of the development of the teaching philosophy and Islamic Philosophy in Malaysia and ends with a discussion on the relevant problems and challenges covering issues concerning the expertise in the field, infrastructure as well as student interest in the programs.